Distribution of Arbuscular Mycorrhiza Fungi (AM Fungi) in different plants within tailings deposition areas of Freeport Indonesia, Timika, Central Papua, Indonesia - IRNANDA AIKO FIFI DJUUNA; NUNANG LAMAEK MAY; SITI HAJAR KUBANGUN; MARIA MASSORA; SOBA WILLEM AIBINI (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Djuuna IAF, May NL, Kubangun SH, Massora M, Aibini SW. 2023. Distribution of Arbuscular Mycorrhiza Fungi (AM Fungi) in different plants within tailings deposition areas of Freeport Indonesia, Timika, Central Papua, Indonesia. Biodiversitas 24: 4515-4522. This study investigated the presence of Arbuscular Mycorrhiza Fungi (AM Fungi) in various vegetation types within tailings deposition areas in Freeport Timika, Papua. Soil and root samples were collected from 41 sampling locations, representing 28 types of vegetation growing in these areas. AM Fungi spores were extracted using the wet sieving technique, while root samples were cleaned, stained, and analyzed for the percentage of root infection using the gridlines method. Some soil characteristics were also analyzed, including pH (H2O), moisture content, organic carbon (C), Total nitrogen (N) and phosphorus (P), and soil texture. The study showed low total soil N and P levels, with organic C ranging from low to high and a pH range from 6 to 6.7. The spore number ranged from 2 to 20 spores/10 g soil, and the percentage of root colonization varied from 17 to 89.5%. The highest number of spores (20 spores/10 g soil) was found in the rhizosphere of Homalanthus sp. and Polyalthia glauca, while the highest percentage of root colonization (89.5%) was observed under Pandanus sp. at Upper ADA. Notably, the highest number of spores did not correspond to the highest percentage of infected roots. Additionally, four genera of AM Fungi, namely Glomus, Acaulospora, Scuttelospora and Gigaspora, were found to thrive in tailings areas and have the potential to be developed as biofertilizers for tailings rehabilitation programs.